Improving the track friendliness of a four-axle railway vehicle using an inertance-integrated lateral primary suspension. Issue 1 (2nd January 2021) - Lewis, T. D.; Li, Y.; Tucker, G. J.; Jiang, J. Z.; Zhao, Y.; Neild, S. A.; Smith, M. C.; Goodall, R.; Dinmore, N.
Abstract : Improving the track friendliness of a railway vehicle can benefit the railway industry significantly. Rail surface damage in curves can be reduced by using vehicles with a lower Primary Yaw Stiffness (PYS); however, this can reduce high-speed stability and worsen ride comfort. Previous studies have shown that this trade-off between track friendliness and passenger comfort can be successfully combated by using an inerter in the primary suspension; however, these utilise simplified vehicle models, contact models, and track inputs. Considering a realistic four-axle passenger vehicle model, this paper investigates the extent to which the PYS can be reduced with inertance-integrated primary lateral suspensions without increasing root-mean-square (RMS) carbody lateral accelerations. The vehicle model, with these enhanced suspensions, has been created in VAMPIRE ®, with the dynamics being captured over a range of vehicle velocities and equivalent conicities. Based on systematic optimisations using network-synthesis theory, several beneficial inertance-integrated configurations are identified, and the PYS can be reduced by up to 47% compared to the default vehicle (a potential Network Rail Variable Usage Charge saving of 26%), without increasing RMS carbody lateral accelerations. Further simulations are performed to investigate the vehicle's performance in curve transitions and when subject to one-off peak lateral track irregularities.